Build an app and they will come? Lessons learnt from trialling the GetThereBus app in rural communities. Issue 3 (4th January 2018) - Corsar, David; Cottrill, Caitlin; Beecroft, Mark; Nelson, John D.; Papangelis, Konstantinos; Edwards, Peter; Velaga, Nagendra; Sripada, Somayajulu
Abstract : Real‐time passenger information (RTPI) systems have been identified as having benefits in terms of passenger willingness to travel by public transport and their satisfaction levels with services provided. The lack of this amenity in rural areas, however, may hamper public transport use, thus reinforcing patterns of over‐reliance on personal vehicles. To explore the potential impacts of providing RTPI in rural areas, a smartphone application ( GetThereBus ) was developed to allow rural bus passengers to share real‐time public transport data, and access real‐time and timetable information. Through user testing of GetThereBus, this work aimed to address questions related to the impact of the limited availability of rural digital infrastructure on the provision of RTPI; the potential for crowdsourced information to supplement published timetable information given digital limitations; and the potential impacts of such a system on the traveller experience. This study describes the GetThereBus development and evaluation phases. The authors found it was possible to design and develop a system that overcame many of the technological limitations experienced in rural areas, and users reported a positive response to the system. However, despite a campaign of user engagement, it proved difficult to recruit and motivate sufficient users to provide the data needed to achieve area‐wide coverage.